The zinc‐binding nuclear protein HIPP3 acts as an upstream regulator of the salicylate‐dependent plant immunity pathway and of flowering time in Arabidopsis thaliana. Issue 4 (24th April 2015) - Zschiesche, Wiebke; Barth, Olaf; Daniel, Katharina; Böhme, Sandra; Rausche, Juliane; Humbeck, Klaus
Summary: Biotic and abiotic stress responses of plants are linked to developmental programs. Proteins involved in different signaling pathways are the molecular basis of this concerted interplay. In our study, we show that Arabidopsis thaliana HEAVY METAL‐ASSOCIATED ISOPRENYLATED PLANT PROTEIN3 (HIPP3; At5g60800) acts as an upstream regulator of stress‐ and development‐related regulatory networks. Localization, metal‐binding and stress‐responsive gene expression of HIPP3 were analyzed via microscopy, protein and inductively coupled plasma (ICP)‐MS analyses and quantitative real‐time PCR. In addition, transcriptome and phenotype analyses of plants overexpressing HIPP3 were used to unravel its function. Our data show that HIPP3 is a nuclear, zinc‐binding protein. It is repressed during drought stress and abscisic acid (ABA) treatment and, similar to other pathogen‐related genes, is induced after infection with Pseudomonas syringae pv. tomato . HIPP3 overexpression affects the regulation of > 400 genes. Strikingly, most of these genes are involved in pathogen response, especially in the salicylate pathway. In addition, many genes of abiotic stress responses and seed and flower development are affected by HIPP3 overexpression. Plants overexpressing HIPP3 show delayed flowering. We conclude that HIPP3 acts via its bound zinc as an upstream regulator of the salicylate‐dependent pathway of pathogen response and is also involved in abiotic stress responses and seed and flower development.